"MECHANISMS OF PSYCHOLOGICAL ENSURANCE OF MARRIAGE STABILITY IN YOUNG FAMILIES IN THE DEVELOPMENT STRATEGY OF UZBEKISTAN" (International journal of artificial intelligence, 2025)
This article provides a scientific analysis of the psychological mechanisms that ensure marital stability in young families within the framework of the social priority areas defined by Uzbekistan’s Development Strategy. The psychological model of family stability, interpersonal communication, emotional maturity, conflict management, and social adaptation are examined in close connection with the Development Strategy’s principle “Strong family – strong society.”